Penelusuran Intelegensi, Minat dan Bakat Bagi Siswa MAN 1 Pidie Jaya Provinsi Aceh - Santoso, Harri; Ali, Jasmadi; Zain, Fajran; Abuzar; Rasyidin, Ulfa; Tunnisa, Fadhila; Al-Humaira, Shufia; Hafli, Nur; Kiki, Cut; Wulandari, Cut Nova Rizki (Proceedings of Annual Conference on Community Engagement, 2022)
One of the success factors of higher education is the match between the interests and talents of students. The survey states that 87% of students in Indonesia feel that they are in the wrong major. It can be influenced by several factors, including: friend’s ask, too many suggestions, parents intimidation and scholarship offer. Kuliah Pengabdian Masyarakat (KPM) aim to introduce higher education system, the importance recognize of intelegence, interest and talent for the students in MAN 1 Pidie Jaya Aceh. This engagement program use 2 approaches with 2 methods namely assessment and intervention. Asessment methods use test technic and inventory namely IQ Test, Interest Test, Talent Test and Personality Test. Intervention Method use training about career, socialization about Interest, Talent and Study in higher education. The result show that 36 students in MAN 1 Pidie Jaya have choosen their study program in accordance with the abilities suggested by the team and have ambition to pursue in higher education such colleges and universities. Therefore, it is recommended that students can choose a study program that has been suggested by team of Psychology Faculty